Health achieving societies: Past discourses, present predilections, and possible future contradictions - Shaffi Fazaludeen Koya; Kesavan R Nayar; Arathi P Rao; Lekha D Bhat (Journal of Public Health and Primary Care, 2021)
Economic growth is not an essential prelude to better health as some countries like Sri Lanka and the Indian state of Kerala have shown. Progressive social policies and investments in the social sector have helped some of these countries in the past. This may be unrelated to the present predilections which could certainly lead to future contradictions, especially in giving rise to new scenarios in public health. We have seen that unrealistic setting of goals, ambitious targets given to an ailing health system, together with a lack of clarity regarding activities can result in poor achievements even with incentives. This is more relevant in the future with the complexity of an epidemiological scenario involving both communicable and noncommunicable diseases. Mere techno-centric packages cannot tackle the complex health issues that India face today, as they ignore the larger structural dimensions of the problem. This is especially important with prolonged old age. This necessitates a focused futuristic vision for the population in general and the elderly in particular with a focus on primary care.